Effects of interlimb asymmetries on acceleration and change of direction speed: a between-sport comparison of professional soccer and cricket athletes - Bishop, C.; Read, P.; Brazier, J.; Jarvis, P.; Chavda, S.; Bromley, T.; Turner, A. (The Journal of Strength and Conditioning Research, 2021)
The first aim of this study was to quantify and compare asymmetries among professional soccer and cricket athletes. The second aim was to examine the association between asymmetries and performance within both groups. Professional soccer (n = 18) and cricket (n = 23) athletes performed single-leg countermovement jumps, single-leg drop jumps (SLDJs), a 10-m sprint, and 505 change of direction speed (CODS) tests. Interlimb asymmetries were calculated as a standard percentage difference, Mann-Whitney U tests conducted to establish systematic bias between groups, and Spearman's r correlations used to establish the relationship between asymmetry scores and speed and CODS performance. Soccer athletes sprinted faster, jumped higher, and had a greater reactive strength index (RSI) score than cricket athletes (p < 0.05). However, cricketers showed reduced ground contact times compared with footballers during the SLDJ (p < 0.05). The cricket group showed significantly greater jump height (asymmetry = 11.49 vs. 6.51%; p = 0.015) and RSI (asymmetry = 10.37 vs. 5.95%; p = 0.014) asymmetries compared with soccer players. These metrics were also associated with slower 505 times in the cricket group only (r = 0.56 -0.74; p < 0.01). These results show that between-limb asymmetries exhibit no association with speed and CODS in elite soccer players but are associated with reduced CODS in elite cricketers. Thus, the reduction of interlimb asymmetries may be of greater consideration when working with cricket vs. soccer athletes.